2017
DOI: 10.1007/s10592-017-0925-y
|View full text |Cite
|
Sign up to set email alerts
|

The genetic characterization of an isolated remnant population of an endangered rodent (Cricetus cricetus L.) using comparative data: implications for conservation

Abstract: reflects its extreme isolation. This factor, coupled with inbreeding and genetic drift, are major threats to JW. A neighbor-joining tree based on mtDNA haplotypes shows that JW clusters among samples representing the Central subgroup that is known from central Germany but that has not yet been identified in Poland. Findings presented here improve our understanding of the spread and diversification of the common hamster. We offer the following hypotheses to explain the observed pattern of mtDNA haplotype distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…As well, nobody found hamsters of the North phylogroup in Ukraine, and central Russia. The recent finding of the North-type haplotype in Poland [ 23 ] represents an isolated population in the southwestern region of Poland, 300 km from eastern Germany, which is populated by North phylogroup hamsters. The authors suggested that this occurred because of recent migration or fragmentation of the North phylogroup's range, which earlier included southwestern districts of Poland, but continued to be allopatric with the E1 range located distinctly eastwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, nobody found hamsters of the North phylogroup in Ukraine, and central Russia. The recent finding of the North-type haplotype in Poland [ 23 ] represents an isolated population in the southwestern region of Poland, 300 km from eastern Germany, which is populated by North phylogroup hamsters. The authors suggested that this occurred because of recent migration or fragmentation of the North phylogroup's range, which earlier included southwestern districts of Poland, but continued to be allopatric with the E1 range located distinctly eastwards.…”
Section: Discussionmentioning
confidence: 99%
“…The hamsters of the phylogroup North inhabit Western Europe and represent two lineages, the Western (Belgium, France, the Netherlands, and southern Germany) and Central (northern regions of Germany). A recent study [ 23 ] also detected the presence of a haplotype of the Central phylogroup in southwestern Poland. The time of isolation of these groups was estimated as 10–15 kya, at the end of the Last Glaciation Maximum.…”
Section: Introductionmentioning
confidence: 93%
“…The analysis of the polymorphism of microsatellite loci had worked well for characterizing the metapopulation structure of individual taxa and their genetic subdivision. This is the most clearly shown by the example with anadromous fish species [4,5], and it is also successfully used in study of mammals [6,7].…”
Section: Introductionmentioning
confidence: 89%
“…For instance, it has been demonstrated that the habitat fragmentation of a small rodent-like the European hamsters can lead to low diversity in the population and threaten the species locally (Reiners et al, 2011). If genetic diversity decreases too much, it can be necessary to introduce animals from other phylogeographic groups to improve the survival chances of the population (Melosik et al, 2017). But to be successful, there are other several prerequisites for population reinforcements to fulfill.…”
Section: Population Reinforcementmentioning
confidence: 99%